Biological control agents colonize litchi fruit during storage and stimulate physiological responses to delay pericarp browning - Zheng, Li; Huang, Shilian; Huang, Jiehao; Deng, Yizhen; Wu, Zhenxian; Jiang, Zide; Yu, Guohui (Frontiers in Microbiology, 2023)
Litchi is an economically important fruit in subtropical countries, but pericarp browning can limit its shelf life outside of controlled storage conditions. Effective and sustainable biological control strategies are needed to protect fruit against postharvest browning. In this study, we show that the four bacterial strains Bacillus licheniformis HS10, B. amyloliquefaciens LI24 and PP19, and Exiguobacterium acetylicum SI17 can delay fruit browning in both laboratory trials (LTs) and field plus laboratory trials (FLTs). Strains HS10, LI24 , PP19 and SI17 showed 47.74%, 35.39%, 33.58% and 32.53% browning-inhibitory efficacy respectively at 180 h in LT. Litchi sarcocarp interior sourced isolate SI17 showed 74.05% inhibit-brown efficacy at 216 h in FLTs, performing better in FLT than in LT. Furthermore, strains PP19 and SI17 colonized the fruit pericarp and increased total phenolic and anthocyanin contents but decreased peroxidase and polyphenol oxidase activity. This is the first report of E. acetylicum (SI17) and B. licheniformis (HS10) strains acting as biological control agents (BCAs) to delay postharvest browning in litchi fruit. We conclude that PP19 and SI17 are promising BCAs against fruit browning, and their application could be effective for prolonging the shelf life of harvested litchi fruit.